2012
DOI: 10.3928/00220124-20120716-89
|View full text |Cite
|
Sign up to set email alerts
|

Staff Practice, Attitudes, and Knowledge/Skills Regarding Evidence-Based Practice Before and After an Educational Intervention

Abstract: Administering self-learning online modules may not be the most effective method for expanding evidence-based practice abilities and knowledge/skills of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 20 publications
5
41
2
Order By: Relevance
“…Twelve studies have been published since 2011 10,11,14,15,18,2026. Of the 20 studies, 17 were pre–post uncontrolled trials,11,12,1420,2226,28,29 and three were controlled trials 10,21,27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies have been published since 2011 10,11,14,15,18,2026. Of the 20 studies, 17 were pre–post uncontrolled trials,11,12,1420,2226,28,29 and three were controlled trials 10,21,27.…”
Section: Resultsmentioning
confidence: 99%
“…Participants of studies were mainly nurses (n=7)1013,19,20,22 and physicians (n=6) 16,17,25–27,29. The remaining studies sampled professionals from mixed disciplines (n=5),15,18,23,24,28 chiropractors (n=1),21 and faculty members from a naturopathic and classical Chinese medicine institution (n=1) 14. Studies tested different educational approaches and interventions that varied in duration, design, and format (workshops, lectures, conferences, journal clubs, tutorials, online sessions, competitions) or a combination of these (multiple interventions, MIs).…”
Section: Resultsmentioning
confidence: 99%
“…Along the same lines, Baumbusch and colleagues 25 reported that students' knowledge and beliefs about adult care improved with 42 hours of theoretical courses and 14 hours of practical courses. Yank and colleagues 19 found that medical residents improved their confidence in using SMS after 26 however, reported that online educational programmes did not affect HCPs' knowledge, skills, or attitudes. Therefore, if similar educational sessions were to be incorporated into academic programmes, the way of delivering it (i.e., classroom vs. online) and its length would need to be carefully investigated.…”
Section: After Attending the Educational And Practical Modulesmentioning
confidence: 99%
“…Utilization of mentors has been shown to be effective in implementing EBP projects, whereas a stand-alone EBP educational intervention was not very effective (Green et al, 2014;Mollon et al, 2012). A recent systematic review of 10 studies reported that multifaceted interventions utilizing mentors improved clinicians' EBP knowledge and beliefs, as well as organizational outcomes (Abdullah et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%